2021
DOI: 10.3390/polym13152404
|View full text |Cite
|
Sign up to set email alerts
|

Improved Cell Morphology and Surface Roughness in High-Temperature Foam Injection Molding Using a Long-Chain Branched Polypropylene

Abstract: Long-chain branched polypropylene (LCB PP) has been used extensively to improve cell morphologies in foaming applications. However, most research focuses on low melt flow rate (MFR) resins, whereas foam production methods such as mold-opening foam injection molding (MO-FIM) require high-MFR resins to improve processability. A systematic study was conducted comparing a conventional linear PP, a broad molecular weight distribution (BMWD) linear PP, and a newly developed BMWD LCB PP for use in MO-FIM. The effects… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 25 publications
0
7
0
Order By: Relevance
“…Hence, how to improve the melt strength and foaming behavior of the PP is always a research hotspot. In general, the methods of in situ fibrillated, adding nanoclay, and long-chain branches were used to improve the melt strength of the PP matrix. Moreover, our previous works found that the novel hollow hierarchical structure, which had excellent filtration characteristics, can be prepared through the adjustment of miscible systems like PP copolymer and high melt strength PP (HMSPP), but whether the polymer composites systems can produce the hollow radially gradient porous structures and its functional mechanism still needs to be further studied.…”
Section: Introductionmentioning
confidence: 99%
“…Hence, how to improve the melt strength and foaming behavior of the PP is always a research hotspot. In general, the methods of in situ fibrillated, adding nanoclay, and long-chain branches were used to improve the melt strength of the PP matrix. Moreover, our previous works found that the novel hollow hierarchical structure, which had excellent filtration characteristics, can be prepared through the adjustment of miscible systems like PP copolymer and high melt strength PP (HMSPP), but whether the polymer composites systems can produce the hollow radially gradient porous structures and its functional mechanism still needs to be further studied.…”
Section: Introductionmentioning
confidence: 99%
“…Microcellular injection technology [ 24 , 25 , 26 ] is a special process to overcome some problems that the conventional injection molding cannot. Most of the microcellular foam plus GCP technology [ 27 , 28 ] emphasizes improving surface roughness problems. Very few papers discuss the effect of GCP on the flow length, tensile property, and gas penetration problem.…”
Section: Introductionmentioning
confidence: 99%
“…In this study, the surface quality of microcellular foam is controlled using a pressure–temperature path control method. Prior studies only discussed the effects of temperature [ 27 ] or pressure [ 16 ]. This study investigates combined effects by temperature and pressure, aiming at optimizing parts’ surface quality in the foaming process.…”
Section: Introductionmentioning
confidence: 99%
“…[28] The surface defects of the microcellular injection molded foam make it difficult to use as appearance parts. [29,30] Thus, researchers are trying to withdraw the mold core and open the mold cavity for a distance to prepare the microcellular injection molded PP Glass fiber 20% 64.29% Mechanical property, foam structure [40] BMWD LCB PP UC CBA 2% -Surface roughness, mechanical property [42] PP PTFE 5% 95% Thermal conductivity, foam structure [43] LCB PP POE 20% -Mechanical property [44] co-PP --58% Foam structure, foaming behavior [29] foam with a high expansion ratio, very low density, as well as maintain the characteristics of microcellular injection molding products. [24,31] Wu et al [32] explored mold opening foam with a chemical foaming agent, and investigated the mechanical properties and weight reduction.…”
Section: Introductionmentioning
confidence: 99%